2016
DOI: 10.3390/mi7090148
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a New Tuning Fork Structure for Resonant Pressure Sensor

Abstract: This paper presents a micromachined resonant pressure sensor. The sensor is designed to optimize the sensitivity and reduce the cross-talk between the driving electrodes and sensing electrodes. The relationship between the sensitivity of the sensor and the main design parameters is analyzed both theoretically and numerically. The sensing and driving electrodes are optimized to get both high sensing capacitance and low cross-talk. This sensor is fabricated using a micromachining process based on a silicon-on-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Resonant pressure micro sensors, which are featured with high resolutions, high accuracies, excellent long-term stabilities, and quasi-digital outputs, are widely used in the fields of industrial control, aerospace aviation, and meteorology [1,2,3,4]. As to excitation and detection of resonators, resonant pressure sensors can work based on electrothermal excitation/piezoresistive detection [5,6], electrostatic excitation/capacitive detection [7,8], electromagnetic excitation/electromagnetic detection [9,10], and electrostatic excitation/piezoresistive detection [11,12]. Compared with other types of resonant pressure sensors, the sensors based on electrostatic excitation/piezoresistive detection are featured with high SNRs and simple structures, and thus this type of resonant pressure sensor is under the intensive studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Resonant pressure micro sensors, which are featured with high resolutions, high accuracies, excellent long-term stabilities, and quasi-digital outputs, are widely used in the fields of industrial control, aerospace aviation, and meteorology [1,2,3,4]. As to excitation and detection of resonators, resonant pressure sensors can work based on electrothermal excitation/piezoresistive detection [5,6], electrostatic excitation/capacitive detection [7,8], electromagnetic excitation/electromagnetic detection [9,10], and electrostatic excitation/piezoresistive detection [11,12]. Compared with other types of resonant pressure sensors, the sensors based on electrostatic excitation/piezoresistive detection are featured with high SNRs and simple structures, and thus this type of resonant pressure sensor is under the intensive studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…As reported 12 , in the out-of-plane resonant mode, the vibration direction of the resonator is perpendicular to the diaphragm, resulting in substantial energy loss from the resonator to the diaphragm, which will decrease the Qfactor. Even for the in-plane common side mode, there is still a reaction force that is transferred to the diaphragm from the resonator due to the unbalanced dynamic structure; the quality factor will also be influenced by the diaphragm conditions, such as the width and thickness.…”
Section: Design Of the Resonant Pressure Sensor Chipmentioning
confidence: 91%
“…Resonant pressure sensors based on capacitive detection methods have attracted considerable attention from researchers because they are easy to fabricate and have simple structures 4,6,12,13 . Ren et al 13 proposed a resonant pressure sensor on the basis of the principle of the capacitive detection method; the sensor showed a sensitivity of 8 Hz/kPa with a silicon on insulator wafer, and its total accuracy exceeded 0.05% full scale (FS), but the quality factor was small because a vacuum package was not used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensor uses a hammock resonator as a sensing element and the Q-factor is insensitive to the leakage of cavity gases due to the laterally driven principle. Due to the benefits of being laterally driven, Sun et al presented a micromachined resonant pressure sensor based on an electrostatic excited/capacitance detected resonator in 2016 [20]. Experiment results showed that the sensor had a pressure sensitivity of ~29 Hz/kPa, a nonlinearity of 0.02% FS, a hysteresis error of 0.05% FS within the pressure measurement range of 20 to 280 kPa, and the temperature sensitivity of the resonator was ~2 Hz/°C in the temperature range of −40 to 80 °C.…”
Section: Introductionmentioning
confidence: 99%